ChemInform Abstract: Multidimensional Perovskites: A Mixed Cation Approach Towards Ambient Stable and Tunable Perovskite Photovoltaics. Issue 45 (October 2016) - Koh, Teck Ming; Thirumal, Krishnamoorthy; Soo, Han Sen; Mathews, Nripan
Abstract: Review: [92 refs.